(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2014)
The paper focuses on the structure of contract in Athenian law and the liability to comply with. After a short outline of the meaning and the practical relevance of ‘consensual contracts’ in classical Roman law and their further development in late Antiquity up to modern times the one-century-old controversy about contract in ancient Greek law is resumed: on the one hand the ‘consensualists’ hold that the verb homologein (literally “speak the same”) means “promise to comply with debts.” On the other hand the ‘realists’ argue that the binding force of a contract was not created by a simple promise, but rather through a real basis. The debtor was only liable when he had accepted some goods or assets from the creditor and was frustrating the purpose, for which the creditor had rendered them to him, the so-called ‘Zweckverfügung’ (disposition for a certain purpose, Hans Julius Wolff). One of the crucial sources is the nomos on homologein quoted in Hyperides’ speech Against Athenogenes (§ 13). Compared with quotations of similar statutes (Dem. 42.12, 56.2) it will turn out that in technical sense homologein was only related to court procedure: “in whatever regard someone says the same as another, this is definitive (in the law court)” and did not create obligations.